2002
DOI: 10.1111/j.1432-2277.2002.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cells play an important role in the cytokine production and activation of nuclear factors of liver grafts from non-heart-beating donors

Abstract: In the non-heart-beating donor (NHBD) deterioration of microcirculation of the liver graft is strongly associated with secretion of cytokines and eicosanoids. In this study we investigated the excretion of cytokines, eicosanoids, and DNA binding activity of transcription factors in the grafts from NHBD and evaluated the effects of the elimination of Kupffer cells on them. The purpose of this study was to clarify the impact of Kupffer cells on transcription factor activity and the that of cytokine and eicosanoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…Similar results have been previously described [15,17,38]. Previous studies have also reported reduced amounts of TxB 2 release after Kupffer cell depletion in the setting of isolated liver perfusion and transplantation [50,51]. Our results demonstrated, however, that the elimination of Kupffer cells did not reduce TxB 2 release, but rather increased it.…”
Section: Discussioncontrasting
confidence: 50%
“…Similar results have been previously described [15,17,38]. Previous studies have also reported reduced amounts of TxB 2 release after Kupffer cell depletion in the setting of isolated liver perfusion and transplantation [50,51]. Our results demonstrated, however, that the elimination of Kupffer cells did not reduce TxB 2 release, but rather increased it.…”
Section: Discussioncontrasting
confidence: 50%
“…During the process, the injury of vascular endothelial cells and activation of the Kupffer cells induce the release of endotoxin and cytokines, produces massive iNOS, and then iNOS-induced NO damages the histiocytes [4] . In addition, lack of ATP in hepatic cells brings intracellular calcium overload, activates calcium dependent protease, and then produces xanthione oxidase.…”
Section: Effect Of Preservation Solution On No Expressionmentioning
confidence: 99%
“…It could result in excessive intracellular calcium [20], increasing free oxygen radicals in activated neutrophils and Kupffer cells and apoptosis in liver parenchymal cells [21,22]. Using proteomics technology, Hirsch et al [23] identified 1559 proteins in an HIRI model and found that IR caused certain inflammation-related proteins, such as calgranulin, C3, myeloperoxidase, copper/zinc superoxide dismutase, and hydrogen peroxide, to be up-regulated.…”
Section: Discussionmentioning
confidence: 96%